PERTUMBUHAN EKONOMI DAN KEMISKINAN DI INDONESIA - Ahmad Soleh (UNIVED Press, 2014)
Ahmad Soleh; Economic Growth and Poverty in Indonesia. Purpose of this observation to find out economic growth and poverty in Indonesia using secondary data obtained from Badan Pusat Statistik. During observation period in 2001-2011, the economic growth in Indonesia tend to enhancement experience with growth average 5,33% by year whereas the poverty population percentage in Indonesia is tend to reduction experience with average point 16,13% by year.The high economic growth be expected able to increasing welfare society but the high economic growth in one region not guarantee society welfare in that region, as the phenomenon that happen in West Papua Province which have the highest economic growth average in national (11,27% annually) but the poverty society percentage in West Papua occupy second position (35,77%), this position is after Papua Province. This phenomenon show the economin growth that not take sides at poverty society. Kawasan Barat Indonesia (KBI) has a adequately better condition if it compared with Kawasan Timur Indonesia (KTT) whether is view from economic growth indicator although view from the poverty. The KBI economic growth average is 5,45% annually and it’s above of average national economic growth and the percentage of poverty society is 43% while KTI is 57%. Generally Kawasan Timur Indonesia (KTI) and some region that incorporated in that region and included in left behind category. Necessarily, government should taking seriously and also make serious effort to decrease the disparity of development between territory and region economic growth acceleration, and also increase programs poverty reduction because it will take an effect to Indonesia economic matters entirely. Kata Kunci: Pembangunan,Disparitas,Pertumbuhan Ekonomi, dan Kemiskinan